GESTIÓN INTEGRAL DE RESIDUOS SOLIDOS Y TURISMO SOSTENIBLE EN LA RUTA DEL RIO DEL CANTÓN QUEVEDO - RODRIGUEZ ROMERO MEYBOL DEYANERA (2024)
The research Project focused on the integrated managament of solid waste and sustainable tourism in the Ruta del Río in the Canton of Quevedo, using a qualitative and quantitative methodology, which allowed an in-depth analysis of the information collected on key points such as solid waste management practices , the participation of the businesses that are part of the Ruta del Río, highlighting its impact on natural resources and sustainable tourism activity in the canton. The research sought to recommend several estrategias to strengthen sustainable tourism development achieving economic and environmental benefits, emphasizing the importance of conserving natural resources to avoid a negative impact and improve the quality of life of those involved in addition to adapting better measures for the collection process of these wastes.